Annual Plan 1970-71 Statistical Statements Planning Department Punjab - Planning Commission (Planning Commission, 1971)
Agricultural Production Minor Irrigation Soil Conservation Area Development Large and Medium Industries Transport and Communication Tourism Improved Seed Programme Manures and Fertilizers Plant Protection Agricultural Implements Commercial Crops Extension Training and Farmers Education Agro Industries Corporation Warehousing Extension Training and Farmers Education.
Planning Department Punjab
Planning Department Punjab
Keywords: Agricultural Production; Minor Irrigation; Ayacut Development Programme; Dairying and Milk Supply; Multipurpose Project; Anti-water logging; Drainage and Flood Control; Power Projects; Industrial Training; Printing; Statistics; Publicity